Unveiling Potentials and Overcoming Obstacles: Exploring the Feasibility of Green-Hybrid Conference Management Post-Covid-19 in Bali - Tirtawati, Diah Permana; Sunarta, I Nyoman; Mananda, I Gusti Putu Bagus Sasrawan; Wiranatha, Agung Suryawan (Jurnal Kajian Bali (Journal of Bali Studies); Vol 14 No 1 (2024): ARTICULATING IDENTITYDO - 10.24843/JKB.2024.v14.i01.p06, 2024)
Over the past four decades, Bali has emerged as a leading MICE (Meetings, Incentives, Conferences, Exhibitions) tourism destination. This study examines the feasibility of organizing green-hybrid conferences in Bali post Covid-19, focusing on identifying key potentials and obstacles for effective management. Employing qualitative methods, utilizing interviews and document analysis, the research assesses infrastructure, human resources, and logistical aspects relevant to hosting such conferences. Bali demonstrates adequate infrastructure and human resources but encounters challenges like technological limitations and logistical dependence. These findings shed light on the complexities of implementing green-hybrid conference management post-pandemic. The study’s limitation lies in its focuses solely on Bali, thus potentially limiting generalizability. Nonetheless, it emphasizes collaborative stakeholder efforts and sustainable practices integration in conference management. It highlights the importance of investing in technology and local capacity building to improve feasibility. Future research could explore other destinations’ experiences regarding long term economic and environmental impacts of green-hybrid conference initiatives.